Benchmarking de la investigación de universidades católicas de España, América Latina y el Caribe: el camino hacia un Observatorio de Evaluación Científica de Universidades Católicas (OECUC) - Valderrama-Zurián, Juan-Carlos; Aguilar-Moya, Remedios; Melero-Fuentes, David (Consorcio Iberoamericano para la Educación en Ciencia y Tecnología (ISTEC), 2018)
The publication of the direct results of an investigation is understood as the main product of the research activity. In this framework, obtaining rankings and indicators allows to guide investments and other R&D decisions. This study presents a analysis of the activity, impact, visibility and collaboration of Catholic universities in Spain, Latin America and the Caribbean, as well as an international ranking of these universities with Catholic identity and the main links of collaboration between these universities. With this, it is intended to promote the VIII Conferencia Biredial-ISTEC 2018, del 22 al 25 de octubre de 2018, Lima – Perú. http://conferencia.pucp.edu.pe/biredial-istec 3 research of the community of these universities, as well as to facilitate the possibility of integrating into emerging or consolidated groups, foster relations between universities in common lines of research, and encourage patronage and public or private financing in developed research projects.
VIII Conferencia BIREDIAL – ISTEC 2018. Del 22 al 25 de octubre de 2018. Organizado por la Pontificia Universidad Católica del Perú, Universidad de Costa Rica, Universidade Federal do Rio Grande do Sul, Universidad Autónoma de San Luis Potosí, Universidad Nacional de La Plata, Universidad del Rosario, Universidad del Norte, y el Consorcio Iberoamericano para la Educación en Ciencia y Tecnología (ISTEC). Lima Perú
Keywords: Benchmarking; Investigación en universidades; Hispanoamérica; Universidades católicas; Ranking de universidades; Evaluación científica; http://purl.org/pe-repo/ocde/ford#5.08.02